2013
DOI: 10.5194/bg-10-3649-2013
|View full text |Cite
|
Sign up to set email alerts
|

<sup>90</sup>Sr and <sup>89</sup>Sr in seawater off Japan as a consequence of the Fukushima Dai-ichi nuclear accident

Abstract: Abstract. The impact of the earthquake and tsunami on the east coast of Japan on 11 March 2011 caused a loss of power at the Fukushima Dai-ichi nuclear power plant (NPP) that resulted in one of the most important releases of artificial radioactivity into the environment. Although several works were devoted to evaluating the atmospheric dispersion of radionuclides, the impact of the discharges to the ocean has been less investigated. Here we evaluate the distribution of Fukushima-derived 90Sr (n = 57) and 89Sr … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 21 publications
6
66
1
1
Order By: Relevance
“…This evaluation is, however, strongly dependent on the estimation of the 137 Cs liquid releases as the 90 Sr / 137 Cs activity ratios observed in seawater offshore Fukushima were used for the evaluation of the 90 Sr source term. Recently, Casacuberta et al (2013), analyzing 90 Sr in seawater samples collected in the NW Pacific Ocean during June 2011 (the KOK cruise, Buesseler et al, 2012), estimated the 90 Sr source term to be 0.09-0.9 PBq, which is very similar to that of Povinec et al (2012).…”
supporting
confidence: 68%
“…This evaluation is, however, strongly dependent on the estimation of the 137 Cs liquid releases as the 90 Sr / 137 Cs activity ratios observed in seawater offshore Fukushima were used for the evaluation of the 90 Sr source term. Recently, Casacuberta et al (2013), analyzing 90 Sr in seawater samples collected in the NW Pacific Ocean during June 2011 (the KOK cruise, Buesseler et al, 2012), estimated the 90 Sr source term to be 0.09-0.9 PBq, which is very similar to that of Povinec et al (2012).…”
supporting
confidence: 68%
“…This conclusion is further supported by the 90 Sr measurements at the KOK stations (Casacuberta et al, 2013). The distribution of 90 Sr, which is much less volatile than 137 Cs and thus came almost entirely from the oceanic source, is similar to that for 137 Cs, suggesting that both chemicals came from the same source.…”
Section: Source Amplitudessupporting
confidence: 56%
“…This conclusion is supported by the radium-based analysis of Charette et al (2013), who reported a strong coastal signature in waters sampled during the KOK cruise. The result is further supported by the similarity between the measured 90 Sr and 137 Cs patterns, which suggests that both radionuclides came from the oceanic source (Casacuberta et al, 2013).…”
Section: Summary and Discussionmentioning
confidence: 57%
“…Strontium‐90 is present in surface soil around the world mainly as a result of fallout from past atmospheric nuclear weapons tests, as well as nuclear plant accidents . Moreover, strontium as an element is relatively mobile and can move down with percolating water to underlying layers of soil and into groundwater . The maximum contaminant level allowable by the United States Environmental Protection Agency (EPA) for 90 Sr in public drinking water supplies is 0.33 Bq L −1 (USEPA, 2008) .…”
Section: Introductionmentioning
confidence: 99%